Analysis of Practicum System in The Science Laboratories at FKIP Mulawarman University Toward Perception and Outcome - Andina Armelia; Andhika Aditiya Pratama; Jusriadi Jusriadi; Rabiatul Adawiyah; Vika Yulinda Antika; Nurul Fitiriyah Sulaeman (FKIP ULM, 2023)
A laboratory is a facility schools must own to support the teaching and learning process in schools or tertiary institutions. This research aims to analyze the perceptions and the outcomes obtained by the students from practicum activities at the Science Laboratory at FKIP UNMUL, namely the biology laboratory, chemistry laboratory and physics laboratory. This research employed a qualitative method in which the data were collected via interviews with laboratory assistants and questionnaires to Physics Education students in Batch 2022. The data analysis technique used in this research was quantitative descriptive analysis which described the data collected. Based on the research findings, it can be concluded that the practicum system in the three laboratories is nearly identical, including the preparation, the praticum, and the evaluation after the practicum. However, the perceptions of the students and the results obtained from the practicum are different, meaning that the students tend to understand the practicum only in a certain laboratory.